Inovasi Pemanfaatan Belimbing Wuluh Menjadi Cemilan Sehat - Sahrul Hasan; Rusman Rusman; Nur Ahda Syamsuryani; Hamdani Hamdani; Iyan Febrian; M. Reja Firdaus; Arum Awaliyah; Riski Baitul Alamsyah; Atika Apriyani; Fajrin Fajrin (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Starfruit is a fruit that is rich in nutrients and has various health benefits. However, starfruit is often neglected and not utilized optimally. Therefore, this research aims to develop innovations in the use of starfruit as healthy snacks. The research methods used are experiment and observation. Starfruit is processed into various sweets. These products are then tested for quality, including taste, texture and nutritional value. The research results show that starfruit can be processed into healthy snacks that are delicious and nutritious. Candied starfruit has a unique and savory taste, and has a soft and naturally sweet texture. Starfruit snacks also provide rich vitamin C. Using starfruit as a healthy snack can provide a healthy and nutritious alternative for the people of South Rabangodu. Apart from that, this can also help reduce waste and utilize the potential of starfruit which is often wasted